Hematological Profile and Air Quality: A Case Study in Belendung Subdistrict, Benda, Tangerang - Siti Mimah Rohimah; Nita Noriko; Firman Alamsyah; Dewi Elfidasari; Rizky Nuur Berlianni Mulyanto; Arief Pambudi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Cities with high population density, high traffic volume of public and private transportation, and significant industrial operations in areas surrounding airports constitute a combination that worsens air pollution. Exposure to pollutants could impact the hematological system. The aim of this study is to determine air pollution exposures in Belendung Subdistrict, Benda District, Tangerang. This study served as a preliminary step or pilot study, conducted within a 4.6 km radius of the airport, and located near some industries in the area, using a cross-sectional and purposive method. SO₂, CO, NO₂, Ox as O₃, NMHC, TSP, Pb, PM2.5, and PM10 levels were measured as air pollution variables. These parameters were assessed on the 3rd and 5th days before blood sampling. Neutrophils, eosinophils, monocytes, basophils, lymphocytes, CRP, leukocytes, hemoglobin, erythrocytes, hematocrit, platelets, MCV, MCH, MCHC, and ESR were measured from 12 male and 12 female respondents. The results showed that the air quality ranged within the standard threshold except for PM10, and most residents have normal biomarkers in the blood. This indicated that PM10 merely activates basic immune responses in the body. The observed inflammation provides a correlation between MCH and MCV, with a value of 0.905.